Effectiveness Of Extension Using Booklet Media Toward Between Nutrition Knowledge Children Elementary School 23 Pagar Agung Lahat Regency Year Of 2019 - Sriwiyanti Sriwiyanti; Detiana Detiana (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Elementary school children are important human resources in the nation's success, biologically a group that is prone to food and nutritional deficiencies because they are at a level of growth and development, there are various conditions of unsatisfactory school children such as underweight, anemia of iodine deficiency , lack of appetite, irregular eating patterns. School children are a group that easily receives nutrition education through their schools. This study aims to determine the effectiveness of the use of booklet media on respondents' balanced nutrition knowledge. The study design was a quantitative Quasy-experimental one group Pre-test post-test. The research sample with a total sampling technique is all children of grade V 23 Lahat state primary school. The measuring instrument used was a questionnaire.